Chemotherapy-Induced Nausea and Vomiting in Italian Cancer Centers: Results of CINVDAY, a Prospective, Multicenter Study. Issue 6 (November 2014) - De Tursi, Michele; Carella, Consiglia; Tomao, Silverio; Cinieri, Saverio; Lorusso, Vito; Marchetti, Paolo; Vecchio, Stefania; Sansoni, Elisabetta; Contu, Antonio; Adamo, Vincenzo; Silvestris, Nicola; Nuzzo, Antonio; et al.
Purpose: Guideline consistency in the prevention of chemotherapy-induced nausea and vomiting (CINV) remains low (29% in the Pan European Emesis Registry study) and very low (11%) in regimens with a high emetogenic risk. The aim of this study was to evaluate the guideline consistency of CINV prophylaxis for acute emesis in daily clinical practice in Italy. Methods: This was a prospective, observational, multicenter study. Patients scheduled to receive antitumor treatment on a single prespecified day were included. Data on patient characteristics (demographic and clinical), type of anticancer therapy, and type of antiemetic therapy prescribed for acute emesis were collected on electronic data capture forms. Chemotherapy regimens and antiemetic prophylaxis were categorized according to the MASCC 2011 guidelines. The study was approved by the local ethics committees. Results: From July 2013 to February 2014, a total of 502 patients were enrolled at 26 study sites. Median age was 62 years (range 27–87 years). Colorectal cancer and breast cancer were the most common malignancies. The emetogenic potential of the chemotherapy regimens used was high (HEC) (23.7%), moderate (MEC) (40.6%), low (31.3%) or minimal (4.4%). Overall, guideline consistency was 19.3%. Consistency reached 45% when the various 5HT3 receptor antagonists were considered equivalent and interchangeable in MEC regimens. Adherence to guidelines was lowest for MEC and MINIMAL risk groups. Ten percent of patients in HEC and MEC regimens did not receive any 5HT3 receptor antagonists. NK1 receptor antagonists were used in 8% of all regimens. Conclusions: Our study indicates that antiemetic guideline inconsistency remains an issue in daily clinical oncology practice in Italy.